The effect of rock hardness and integrity on the failure mechanism of mortar bolt composite structure in a jointed rock mass. (January 2023) - Yi, Wenhao; Wang, Mingnian; Zhao, Siguang; Tong, Jianjun; Liu, Chen
Highlights: Three failure modes were observed for each of the joint rock and bolt-grout composite structure during the mortar bolt pull-out process. The pull-out load and displacement curves can be divided into three stages: elastic deformation, plastic deformation and failure. The coupling effect of rock hardness and rock mass integrity effectively influence the mortar bolts anchorage performance. The calculation formulas of ultimate pull-out load and ultimate displacement of mortar bolts in joint rock are established. Abstract: The appearance of joints in the rock tunnels makes the rock mass show obvious anisotropy and discontinuity in physical and mechanical properties, which has a significant influence on the rock mass stability. As one of the normally used support structures in tunnel construction, Mortar bolts will inevitably pass through the joints during the process. Both rock hardness and rock mass integrity will directly affect the anchorage performance of mortar bolts in joint rock. Considering this, this paper designs a mortar bolt pull-out experiment to investigate the joint rock failure modes and bolt-grout composite structure failure modes under different conditions of rock hardness and rock mass integrity. By taking the two influencing factors of rock hardness and integrity into account, the calculation formulas of ultimate pull-out load and ultimate displacement of mortar bolts in joint rock are established and proposed.